2015
DOI: 10.1111/ans.13036
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio as predictor of mortality and morbidity in cardiovascular surgery: a systematic review

Abstract: Elevated NLR were associated with increased long-term mortality and morbidity after major cardiac and vascular surgery. NLR may guide perioperative management and risk-stratification of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 48 publications
4
77
2
6
Order By: Relevance
“…Most studies evaluating NLR and PLR for cardiac surgery showed predictive value of these markers before surgery,19 similar to our study in HTX. One study, however, showed that both pre‐operative and post‐operative (48 h) higher NLR values were associated new atrial fibrillation in patients undergoing CABG 20.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies evaluating NLR and PLR for cardiac surgery showed predictive value of these markers before surgery,19 similar to our study in HTX. One study, however, showed that both pre‐operative and post‐operative (48 h) higher NLR values were associated new atrial fibrillation in patients undergoing CABG 20.…”
Section: Discussionsupporting
confidence: 90%
“…A systemic inflammatory response leads to angiogenesis, inhibition of apoptosis, and DNA damage. The NLR is a factor related to systemic inflammation [28,29]. A high NLR means a relatively elevated neutrophil count and depletion of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, it has been difficult to differentiate between the normal beneficial inflammatory response needed for healing and components of the inflammatory response that can be linked to disease progression. There is increasing evidence that changes in circulating leukocytes associated with disease hold important prognostic information that could be used clinically (15). In particular, cardiopulmonary bypass (CPB), which is used extensively in patients undergoing heart surgery, has often been suggested as an important inflammatory stimulus responsible for significant changes in leukocytes that remain poorly defined (6–8).…”
Section: Introductionmentioning
confidence: 99%